2020
DOI: 10.1111/1462-2920.14941
|View full text |Cite
|
Sign up to set email alerts
|

GPI7‐mediated glycosylphosphatidylinositol anchoring regulates appressorial penetration and immune evasion during infection of Magnaporthe oryzae

Abstract: Summary Glycosylphosphatidylinositol (GPI) anchoring plays key roles in many biological processes by targeting proteins to the cell wall; however, its roles are largely unknown in plant pathogenic fungi. Here, we reveal the roles of the GPI anchoring in Magnaporthe oryzae during plant infection. The GPI‐anchored proteins were found to highly accumulate in appressoria and invasive hyphae. Disruption of GPI7, a GPI anchor‐pathway gene, led to a significant reduction in virulence. The Δgpi7 mutant showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Precursor proteins are typically inactive and are converted into mature functional proteins through a series of PTMs, which modulate diverse protein properties and functions (Deribe et al, 2010). In phytopathogens, some protein modifications play important roles in development and pathogenesis, including sumoylation, N‐glycosylation, glycosylphosphatidylinositol (GPI), and acetylation (Liang et al, 2018a; Liu et al, 2020; Chen et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Precursor proteins are typically inactive and are converted into mature functional proteins through a series of PTMs, which modulate diverse protein properties and functions (Deribe et al, 2010). In phytopathogens, some protein modifications play important roles in development and pathogenesis, including sumoylation, N‐glycosylation, glycosylphosphatidylinositol (GPI), and acetylation (Liang et al, 2018a; Liu et al, 2020; Chen et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mutants in glycosylation pathway genes often induce a strong host immune response. For example, mutants affecting N‐ glycosylation and GPI anchoring pathway genes induce host cell ROS accumulation (Chen et al ., 2014; Liu et al ., 2020), suggesting that cell wall modifications dependent on glycosylation may be important in preventing PAMP‐triggered immunity. This also suggests that secreted effector proteins involved in immunity suppression, particularly in the apoplastic compartment, may require glycosylation for their activity.…”
Section: Regulatory Mechanisms Of Glycosylation In Biotrophic Establishment During Fungal Growth and Proliferationmentioning
confidence: 99%
“…Several studies have also addressed the roles of GPI anchoring during infection by plant pathogenic fungi (Rittenour & Harris, 2013; Oliveira‐Garcia & Deising, 2016; Liu et al ., 2020). To date, only a few GPI anchoring pathway‐related genes have been successfully deleted in fungi (Table 1).…”
Section: Glycosylation and Fungal Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the IRK-interacting protein is involved in the maintenance and differentiation of the root and shoot meristem [38,39]. In the meantime, marker A4657 has been determined to be located on the glycosylphosphatidylinositol anchor attachment 1 protein gene, and glycosylphosphatidylinositol anchor genes play a key role in many biological processes by targeting proteins to the cell wall; however, its role in plant pathogenic fungi is largely unknown [40]. With this study, it was determined that the glycosylphosphatidylinositol anchor gene is associated with Verticillium wilt.…”
Section: Markers Associated With Non-defoliating Pathotype (Vd11 Isolate) Of Verticillium Wilt Diseasementioning
confidence: 99%